Pelatihan Menggambar sebagai Pendampingan Keterampilan bagi Anak-Anak Tuli di Komunitas â€œPop Joy Signâ€ Jakarta - Gilang Cempaka; Vidya Kharisma; Rio Satriyo Hadiwijoyo; Annisa Rachimi Rizka; Tasri Jatnika; Walid Fauzanul Adzimy (Dikmas: Jurnal Pendidikan Masyarakat dan Pengabdian, 2023)
Deaf children require the ability to draw in order to communicate effectively while developing their creativity. Visual Communication Design Study Program (DKV) Paramadina University in collaboration with a community that cares for the deaf, namely Pop Joy Sign (PJS), collaborates to organise community service activities (PkM) by providing basic drawing training for deaf children aged 9-14 years. The method used in this PkM is applied in nature by providing drawing practices and insight into drawing with Indonesian themes, accompanied by the PkM team and sign language interpreters (JBI). This training uses the total communication method, the concept of communication for deaf people to achieve effective communication, involving both written and visual media, and also JBI. The results demonstrated that all participants have the ability to express their ideas and complete the drawings in a timely manner. The visual language analysis method using Wimba and basic drawing theory shows that in general the participants are able to tell stories in pictorial language, but still need to be improved in terms of skills and imagination. It is hoped that with this training, deaf children will be able to develop their ability to communicate fully through visuals in addition to the sign language they have mastered. Moreover, by drawing, deaf children can become more confident in communication and develop their creativity for the future.